A mass spectrometric study of the acid-catalysed d-fructose dehydration in the gas phase. (2nd September 2015) - Pepi, Federico; Ricci, Andreina; Garzoli, Stefania; Troiani, Anna; Salvitti, Chiara; Di Rienzo, Brunella; Giacomello, Pierluigi
Abstract: 5-hydroxymethylfuraldehyde (5-HMF) and simpler compounds, such as levulinic acid (LA) and glyceraldehyde, are platform molecules produced by the thermal acid-catalyzed dehydration of carbohydrates coming from biomass. Understanding sugar degradation pathways on a molecular level is necessary to increase selectivity, reduce degradation by-products yields and optimize catalytic strategies, fundamental knowledge for the development of a sustainable renewable industry. In this work gaseous protonatedd -fructose ions, generated in the ESI source of a triple quadrupole mass spectrometer, were allowed to undergo Collisionally Activated Decomposition (CAD) into the quadrupole collision cell. The ionic intermediates and products derived from protonatedd -fructose dehydration were structurally characterized by their fragmentation patterns and the relative water-loss dehydration energies measured by energy-resolved CAD mass spectra. The data were compared with those obtained from protonatedd -glucose decomposition in the same experimental conditions. In the gas phase, d -fructose dehydration leads to the formation of a mixed population of isomeric [C6 H6 O3 ]H + ions, whose structures do not correspond exclusively to 5-hydroxymethyl-2-furaldehyde protonated at the more basic aldehydic group. Graphical abstract: Highlights: Gas-phase dehydration of protonatedd -fructose was studied by mass spectrometry. The ionic gaseous intermediates and products were structurally characterized. A mixed population of isomeric [C6 H6 O3 ]H + ions is formed. One possible gas-phase dehydration mechanism ofd -fructose was hypothesized.